Long‐Term Adherence to Modifiable Factors and Incident Cardiovascular Disease Among Women With a History of Gestational Diabetes: A Prospective Cohort Study - Frank Qian; Jiaxi Yang; Deirdre K. Tobias; Sylvia H. Ley; Jorge E. Chavarro; Gang Liu; Zhangling Chen; Edwina Yeung; Qi Sun; Walter C. Willett; Frank B. Hu; Cuilin Zhang (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Women with prior gestational diabetes are at increased risk of cardiovascular disease (CVD), but whether and to what extent this risk is modifiable is unknown. Methods NHSII (Nurses' Health Study II) participants (N=4355), who reported a gestational diabetes diagnosis between 1989 and 2001 and were free of type 2 diabetes, CVD, and cancer at baseline were included. Incident CVD included nonfatal myocardial infarction, fatal coronary heart disease, nonfatal/fatal stroke, angiographically confirmed angina, and coronary revascularizations. Modifiable factors were updated every 2 to 4 years. Optimal modifiable factors included body mass index <25.0 kg/m2, favorable Alternative Healthy Eating Index‐2010 score (top 40%), ≥150 minutes moderate‐intensity or ≥75 minutes vigorous‐intensity physical activity/week, noncurrent smoking, and moderate alcohol intake (5.0–14.9 g/day). Multivariable‐adjusted Cox models were used to estimate hazard ratios (HR) and 95% CIs with CVD. Results During a median 27.9 years of follow‐up, 188 incident CVD events occurred. Compared with women with zero optimal factors, HR for CVD among women with one, two, three, or four optimal factors was 0.56 (95% CI, 0.22–1.42), 0.40 (95% CI, 0.16–1.02), 0.32 (95% CI, 0.12–0.84), and 0.14 (95% CI, 0.05–0.46), respectively (P‐trend<0.0001). There were no incident CVD events in women with all 5 optimal factors. Compared with women with stable modifiable factors, those who increased the number of optimal factors had a lower risk of CVD: 0.30 (95% CI, 0.16–0.55), and those who decreased the number of optimal factors had higher risk: 2.05 (95% CI, 1.28–3.29). Conclusions Long‐term adherence to and improvements in optimal modifiable factors were associated with lower CVD risk after gestational diabetes.